Implementasi Kurikulum 2013 dalam Pembelajaran Fiqih pada Peserta Didik MAS Darul Ihsan Aceh Besar - Maghfira Siantikha, Cut (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2023)
This research is motivated by the issue of lack of still teachers who do not understand the 2013 curriculum so that the implementation of the learning process has not been fully implemented in accordance with the curriculum planned by the government, namely the 2013 curriculum. supervised by the school principal or supervisor and there are teachers who adopt other people's RPP and there are also teachers who experience difficulties when preparing RPPs that are in accordance with the provisions of the 2013 curriculum. In this research the researcher conducted it at one of the Madrasahs in Aceh Besar. This study is to determine the planning and implementation of fiqh learning in the 2013 curriculum at MAS Darul Ihsan, and to determine the evaluation of the 2013 curriculum learning in fiqh learning. This study used qualitative research methods. Data collection through observation, interviews and documentation. The participants consisted of school principals, head of curriculum, teachers of fiqh subjects. The results of the research show that the implementation of the 2013 curriculum in fiqh learning at MAS Darul Ihsan Abu Hasan Krueng Kalee is in good qualifications, because it has fulfilled the 2013 curriculum mechanism. The obstacle is the lack of learning media available in schools such as infocus and TV.